Layered-MnO2 Nanosheet Grown on Nitrogen-Doped Graphene Template as a Composite Cathode for Flexible Solid-State Asymmetric Supercapacitor - Liu, Yongchuan; Miao, Xiaofei; Fang, Jianhui; Zhang, Xiangxin; Chen, Sujing; Li, Wei; Feng, Wendou; Chen, Yuanqiang; Wang, Wei; Zhang, Yining (ACS applied materials & interfaces, 2016)
Flexible solid-state supercapacitors provide a promising energy-storage alternative for the rapidly growing flexible and wearable electronic industry. Further improving device energy density and developing a cheap flexible current collector are two major challenges in pushing the technology forward. In this work, we synthesize a nitrogen-doped graphene/MnO2 nanosheet (NGMn) composite by a simple hydrothermal method. Nitrogen-doped graphene acts as a template to induce the growth of layered δ-MnO2 and improves the electronic conductivity of the composite. The NGMn composite exhibits a large specific capacitance of about 305 F g–1 at a scan rate of 5 mV s–1. We also create a cheap and highly conductive flexible current collector using Scotch tape. Flexible solid-state asymmetric supercapacitors are fabricated with NGMn cathode, activated carbon anode, and PVA–LiCl gel electrolyte. The device can achieve a high operation voltage of 1.8 V and exhibits a maximum energy density of 3.5 mWh cm–3 at a power density of 0.019 W cm–3. Moreover, it retains >90% of its initial capacitance after 1500 cycles. Because of its flexibility, high energy density, and good cycle life, NGMn-based flexible solid state asymmetric supercapacitors have great potential for application in next-generation portable and wearable electronics.